ANALISIS GERAKAN LITERASI SEKOLAH TERHADAP KEMAMPUAN MEMBACA PERMULAAN MENGGUNAKAN MEDIA RODA BACA KELAS II SD - Devi, Devinta Fitri Wijayanti; Sufa, Feri Faila; Hanafi, Muhammad Faruq (Universitas Negeri Medan, 2025)
This research was conducted to analyze: 1) Implementation of the School Literacy Movement (GLS), and 2) Use of reading wheel learning media for early reading in Class II of SDN Geneng 02 Gatak Sukoharjo in the 2024/2025 Academic Year. This research is a qualitative descriptive study. This research uses primary data sources and secondary data sources. The subjects of this research were the Principal, Class II Teacher, and 3 students in Class II with the object of analyzing the GLS Program on Early Reading Skills Using Reading Wheel Media. The data collection techniques used by the researcher were observation, interviews, and documentation. The validity of the data used was source triangulation and technical triangulation. The data analysis used was data collection, data reduction, data presentation, and conclusion drawing. Analysis of the research data obtained by the researcher can conclude that: 1) the implementation of the school literacy movement consists of 3 main stages, namely habituation, development, and learning, with a focus on reading activities for 15 minutes before learning activities begin which are carried out on Mondays and Wednesdays, 2) the use of reading wheel learning media for initial reading in class II has a positive impact on improving students' basic literacy skills, especially in terms of recognizing letters, syllables, and arranging words into simple sentences.